Poor peripheral blood stem cell mobilization affects long‐term outcomes in multiple myeloma patients undergoing autologous stem cell transplantation. Issue 1 (29th May 2017) - Moreb, Jan S.; Byrne, Michael; Shugarman, Ilicia; Zou, Fei; Xiong, Sican; May, William S.; Norkin, Maxim; Hiemenz, John; Brown, Randall; Cogle, Christopher; Wingard, John R.; Hsu, Jack W.
Abstract: Background: Peripheral blood stem cell (PBSC) mobilization is routinely undertaken prior to autologous stem cell transplantation (ASCT) in patients with multiple myeloma (MM). A number of studies have identified risk factors for poor PBSC mobilization, however, little data exists to correlate mobilization with disease‐specific outcomes in this patient population. Prospective work in MM has demonstrated similar outcomes in a homogenous patient population. Methods: In this single institution analysis, we retrospectively studied the impact of poor PBSC mobilization on progression free survival (PFS) and OS in MM patients undergoing PBSC mobilization. Poor mobilizers are defined as patients that collected < 4 × 10 6 CD34 + cells/kg over maximum of 5 apheresis days, or those that required ≥2 mobilization cycles to achieve this target. Results: We confirm that poor PBSC mobilization is significantly associated with a shortened PFS ( P = .0012) and OS ( P = .0005) compared with good mobilizers. Our univariate analysis also shows that independent risk factors for poor mobilization include male gender, higher ideal body weight, and a greater median number of lines of chemotherapy prior to PBSC mobilization. However, by multivariate analysis, only number of prior lines of chemotherapy remains significantly predictive of poor mobilization (Odds ratio 1.857, P = .0095). The use of high‐dose G‐CSF (> 10 mcg/kg/day) and/or plerixafor can significantly improve mobilization and ASCT chances in this population. Discussion: These data indicate that poor mobilization can be predictable and is associated with more aggressive disease biology and worse outcomes, warranting intensive post‐ASCT management.